Inheritance of productive tillering in hybrids of winter feed barley - Darina Dimova; Darina Valcheva (Растениевъдни науки, 2015)
The inheritance of productive tillering in hybrids of winter feed barley was studied. The investigation was conducted during the period 2005 – 2007 at the Institute of Agriculture – Karnobat. In diallel combination attended 6 parents and 30 cross combinations. It has been found that the number of productive tillers is controlled by genetic system, where prevail an additive-dominant action of the genes. In the created hybrids winter feed barley increased productive tillering compared to parents in 6 crosses, where inheritance was incomplete dominance to an overly dominant. Productive tillering in the particular diallel combination had stable genetic control, and was relatively low inﬂuenced by the environmental conditions.